PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KANTOR PELAYANAN PAJAK PRATAMA SEMARANG (Students' Journal of Accounting and Banking, 2015)
The purpose of this study to examine, whether the modernization of the tax administration system in Semarang affect the Tax Office Primary, taxpayer compliance. Modern tax administration system is the adoption of modern tax administration system which is an improvement to the taxpayer and institutions to become more rapid, efficient, and economical. Type of descriptive quantitative research. With a sample of tax officials on the Tax Office Primary Semarang. the sample size is determined by purposive sampling method with a sample of 76 employees taxes. Survey methods used by data collected through a questionnaire with multiple linear regression analysis applied to the data processing SPSS 16.0. The results showed that the partial testing showed variable changes in organizational structure, changes in the implementation of services, facilities that utilize IT services do not have a significant effect on tax compliance, while variable employee code of conduct has a significant influence on tax compliance.Keywords: Changes in Organizational Structure, Modernization Changes In The Implementation of The Service, Service Facility With Information Technology, Employee Code of Conduct, Compliance Taxpayer